Phonological Differences in the Sub-Dialect of Dayak Desa Dawak and Dayak Desa Belungai - Ermina Toliang (Universitas Brawijaya, 2019)
Dayak Desa language has five sub-dialects, namely Dayak Desa Dawak (DDD), Dayak Desa Belungai (DDB), Dayak Desa Ulu, Dayak Desa Meranggau and Dayak Desa Semalak. This research only deals with the analyses of phonological differences in the sub-dialect of Dayak Desa Dawak (DDD) and Dayak Desa Belungai (DDB) that is located in Toba District. The goal is to document the language from a phonological point of view. This research uses a list of 200 Swadesh vocabularies. The participants were asked to pronounce the words in the list and recorded by PRAAT. The result of the recording was verified by the spectrogram. The findings showed differences between the two sub-dialects such as raising the vowel sound in the closed syllable: /ɛ i/, raising the vowel sound in the open syllable: /ɛ ə/, the consonant alteration in the first syllable: /s/ /h/, the consonant alteration in the last syllable: /s h/, /ŋ n/, /r ɾ/ and sound:/ɲ j/, and the consonant insertion in the first syllable: /Ø n/. The difference exemplified by the phoneme /r/ of DDD which changes into /ɾ/ in DDB becomes the special characteristic for DDB.